2020
DOI: 10.1097/ju.0000000000001155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Urology Residency Training: A Nationwide Survey of Program Directors by the Society of Academic Urologists

Abstract: Purpose: Coronavirus disease (COVID-19) has profoundly impacted residency training and education. To date, there has not been any broad assessment of urological surgery residency changes and concerns during the COVID-19 pandemic. Materials and Methods: The Society of Academic Urologists distributed a questionnaire to urology residency program directors on March 30, 2020 exploring residency program changes related to the COVID-19 pandemic. Descriptive statistics are presented. A qualitative analysis of free res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
102
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 13 publications
(17 reference statements)
4
102
0
6
Order By: Relevance
“…Specifically, clinical research was reported to be decreased by 30.7%, increased by 24.6%, and remained the same for 36.5% of respondents. These findings agree with those of other studies reporting an increase in resident research in 26% of training programmes and a decrease in 22% of them [25], suggesting that trainees' increased off-service time led to increased resident productivity in terms of clinical research activities [26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, clinical research was reported to be decreased by 30.7%, increased by 24.6%, and remained the same for 36.5% of respondents. These findings agree with those of other studies reporting an increase in resident research in 26% of training programmes and a decrease in 22% of them [25], suggesting that trainees' increased off-service time led to increased resident productivity in terms of clinical research activities [26].…”
Section: Discussionsupporting
confidence: 92%
“…In a similar study of neurosurgery training, the authors also reported a volume decrease and that many outpatient visits had been transitioned to telemedicine, decreasing resident exposure to outpatients [24]. Additionally, other authors reported that urology residents will not meet minimum case requirements because of COVID-19, while double-scrubbing in the operating room was significantly reduced, thus negatively affecting their surgical exposure [25]. In general, diverse responses were collected regarding research activity during the pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…In a survey of urology program directors, 60% reported concern that their residents may not meet minimum training requirements. 12 Similarly, 2 of 3 program directors in interventional cardiology reported in a recent survey that they are concerned that the pandemic may present a moderate-to-severe impediment to fellowship training. 13 In another survey, more than 60% of plastic surgery residents stated that cutbacks to didactics and practical training would affect their training and professional experience significantly.…”
mentioning
confidence: 99%
“…Despite this response, the virus continued to spread, and the pandemic affected not only healthcare systems but also medical staff, particularly the physicians (Kang et al, 2020). Due to the increased workload during the COVID-19 pandemic, many hospitals required their physicians to work overtime hours and sometimes days to care for COVID-19 patients (Rosen et al, 2020). Additionally, most of the educational programs aimed at physicians, such as conferences and lectures, have stopped.…”
mentioning
confidence: 99%